Determining the Future Demand: Studies for Air Traffic Forecasting Remove - Phyoe, Su Myat (2016)
The world has seen a rapid increase in air traffic and movement of passengers in the past two decades. Within Asia-Pacific itself, the number of aircraft departures saw a growth of approximately 200% in less than 10 years [1]. Air traffic forecast models would be useful in predicting the growth of air traffic in the future, so as to facilitate the development of technology, operations and infrastructure for the aviation industry. This paper aims to study air traffic models and find an approach for forecasting of the air traffic growth in Singapore. This paper applies the forecasting methodologies to predict the air traffic growth and checks the growth within the region by using simulations and modeling.